Supervision and Organizational Resilience: Considerations for Staff Retention in Child Welfare Agencies - Wells, Melissa; Jonsson, Linda S.; Keefe, Mackenzie; Oates, Fiona (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2024)
Objectives: This paper presents results from a mixed methods online survey on factors related to child welfare professionals’ experiences with supervision, considered within the framework of organizational resilience.Methods: This analysis presents results from 543 child protective service (CPS) professionals in the United States.Results: About a quarter of these child welfare professionals currently held supervisory roles. Comparisons of those without supervisory roles indicate higher mean ratings on perceptions of support and care from those not currently in supervisory roles, while those currently in supervisory roles reported higher mean ratings on perceptions of potential growth and promotion. Outcomes including intention to stay in child welfare, satisfaction with position, and salary were significantly associated with positive supervision components. These professionals’ qualitative responses highlight a need for consideration of supervision approaches that reflect trauma-informed components and that foster organizational resilience.Implications: Implementation of these critical supports for child welfare professionals may have lasting impacts on the well-being of children, youth, and families.